2016
DOI: 10.1111/bjd.14897
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to cutaneous melanoma in southern Switzerland: role ofCDKN2A,MC1RandMITF

Abstract: Inclusion criteria for the Ticino population for genetic assessment should follow the rule of two (two affected individuals in a family or a patient with multiple CMs), as we detected a CDKN2A mutation in almost 10% of our pedigrees (four of 41), MITF p.E318K in 7% (three of 41) and a higher number of MC1R variants than in the control population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Although CDKN2A mutations confer an increased risk of melanoma, not all carriers of the mutation develop this pathology, suggesting that other environmental, clinical, and genetic factors contribute to increase the risk of melanoma [26][27][28]. Indeed, when assessing the relationship between geographical location and individual risk of bearing a CDKN2A mutation, it is important to take into account the variability of melanoma incidence in the general population and the degree of penetrance of CDKN2A mutations for each specific country considered [7,16,17]. It appears, in fact, that in regions with higher incidence of melanoma there is a greater possibility of finding multiple family members with melanoma or multiple primary melanomas caused by reasons other than CDKN2A mutations.…”
Section: Cdkn2amentioning
confidence: 99%
See 1 more Smart Citation
“…Although CDKN2A mutations confer an increased risk of melanoma, not all carriers of the mutation develop this pathology, suggesting that other environmental, clinical, and genetic factors contribute to increase the risk of melanoma [26][27][28]. Indeed, when assessing the relationship between geographical location and individual risk of bearing a CDKN2A mutation, it is important to take into account the variability of melanoma incidence in the general population and the degree of penetrance of CDKN2A mutations for each specific country considered [7,16,17]. It appears, in fact, that in regions with higher incidence of melanoma there is a greater possibility of finding multiple family members with melanoma or multiple primary melanomas caused by reasons other than CDKN2A mutations.…”
Section: Cdkn2amentioning
confidence: 99%
“…The genes that predispose to melanoma are classified as low, medium, and high penetrance genes (Table 1) [13][14][15][16][17]. Each of these genes has a different intrinsic mechanism whose mutations can lead to the inactivation of fundamental biological mechanisms regulating cellular integrity.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses included melanoma-prone families and individuals with multiple cutaneous melanomas. A recent study reported the analysis of 27 melanoma-prone families, showing: CDKN2A V126D mutation in 7/27; CDKN2A A148T was observed in 7/27 (this germline mutation was observed in 7/146 normal healthy blood donors); MC1R melanoma-associated polymorphism was detected in 78% of cases (and 66% in healthy donors); the MITF E318K mutant was observed in 7% of cases (and in 0.7% of healthy controls) [ 114 ].…”
Section: Molecular Abnormalitiesmentioning
confidence: 99%
“…A rare functional variant of MITF(E318K) has been shown to disrupt a conserved SUMOylation site and to confer a two-to fourfold risk for cutaneous melanoma 1,2 . Moreover, there have been small studies suggesting that this variant is also associated with other cancers such as renal cell carcinoma (RCC) [1][2][3][4][5][6][7][8][9][10][11][12][13] . However, since epidemiologic observations have documented an association between cutaneous melanoma and many other malignancies, including RCC, it is possible that MITF(E318K) represents a germline "passenger" mutation in these other cancers without directly impacting the risk of these other cancers such as RCC.…”
mentioning
confidence: 99%